Hubungan Pengetahuan dengan Sikap Diet Hipertensi pada Lansia - Meilina Oktaria; Hardono Hardono; Wisnu Probo Wijayanto; Ikhwan Amiruddin (Jurnal Ilmu Medis Indonesia, 2023)
Purpose: The research objective was to determine the correlation between knowledge with attitudes towards hypertension dietary on the elderly at the Public Health Center of Kalibalangan in the North Lampung Regency 2021. Method: The type of research used is quantitative analytical design research with a cross-sectional approach. The population in this research were the elderly who visited the Public Health Center of Kalibalangan, namely 129 elderlies. The sample in this research amounted to 56. Gamma Somer's used in test analysis. Results: The results showed that most of the elderly lack knowledge about hypertension diet, namely 44.6% (25 people), most of the elderly have a good attitude, namely 62.5% (35 people). There is a correlation between knowledge and hypertension diet attitude in the elderly p.value 0.003 (<0.05). There is a positive correlation between knowledge and attitudes and a strong correlation with the gamma coefficient value of 0.606 or 60.6%.